The prevalence of cervical abnormalities: Comparison of youth with perinatally acquired HIV and older women in Botswana - Thabo Phologolo; Mogomotsi Matshaba; Bathusi Mathuba; Keboletse Mokete; Ontibile Tshume; Elizabeth Lowenthal (AOSIS, 2023)
Background: Cervical cancer burden and prevalence of precursor lesions is unknown among young women living with HIV in high prevalence settings. Current cervical cancer screening guidelines in resource-limited settings with high HIV prevalence typically exclude adolescents and young women. After observing two cases of advanced cervical cancer among young women with perinatally acquired HIV, a pilot screening programme was established in Botswana. Objectives: To compare the prevalence of cervical abnormalities in young women with perinatally acquired HIV with women aged 30-49 years, regardless of HIV status. Method: We conducted a cross-sectional study of 30-49-year-old women who had visual inspection with acetic acid screening through the Botswana public sector programme, and youth (aged 15-24 years) with perinatally acquired HIV, at a single referral site between 2016 and 2018. We describe the prevalence of cervical abnormalities in each group as well as the crude prevalence ratio. Results: The prevalence of cervical abnormalities in women 30-49 years of age was 10.9% (95% confidence interval [CI]: 10.4, 11.4), and 10.1% (95% CI: 4.7, 18.3) for youth. The crude prevalence ratio was 1.07 (95% CI: 0.58, 2.01). Conclusion: Inclusion of youth living with HIV in cervical cancer screening services should be considered in settings with a high prevalence of HIV and cervical cancer.